P62 as a therapeutic target for inhibition of autophagy in prostate cancer. Issue 5 (25th January 2018) - Wang, Lei; Kim, Donghern; Wise, James T.F.; Shi, Xianglin; Zhang, Zhuo; DiPaola, Robert S.
Abstract : Background: To test the hypothesis that p62 is an optimal target for autophagy inhibition and Verteporfin, a clinically available drug approved by FDA to treat macular degeneration that inhibits autophagy by targeting p62 protein, can be developed clinically to improve therapy for advanced prostate cancer. Methods: Forced expression of p62 in PC‐3 cells and normal prostate epithelial cells, RWPE‐1 and PZ‐HPV7, were carried out by transfection of these cells with pcDNA3.1/p62 or p62 shRNA plasmid. Autophagosomes and autophagic flux were measured by transfection of tandem fluorescence protein mCherry‐GFP‐LC3 construct. Apoptosis was measured by Annexin V/PI staining. Tumorigenesis was measured by a xenograft tumor growth model. Results: Verteporfin inhibited cell growth and colony formation in PC‐3 cells. Verteporfin generated crosslinked p62 oligomers, resulting in inhibition of autophagy and constitutive activation of Nrf2 as well as its target genes, Bcl‐2 and TNF‐α. In normal prostate epithelial cells, forced expression of p62 caused constitutive Nrf2 activation, development of apoptosis resistance, and Verteporfin treatment exhibited inhibitory effects. Verteporfin treatment also inhibited starvation‐induced autophagic flux of these cells. Verteporfin inhibited tumorigenesis of both normal prostate epithelial cells with p62 expression and prostate cancer cells and decreased p62, constitutive Nrf2, and Bcl‐xL in xenograft tumor tissues, indicating that p62 can be developed as a drug target against prostate cancer. Conclusions: p62 has a high potential to be developed as a therapeutic target. Verteporfin represents a prototypical agent with therapeutic potential against prostate cancer through inhibition of autophagy by a novel mechanism of p62 inhibition.